The Impact of Transformational Leadership on Employees' Deviant Innovative Behaviour - Cheng, Chao; Ali, Dhakir Abbas (International Journal on Recent Trends in Business and Tourism (IJRTBT), 2025)
Introduction: China’s economic recovery and increasing competition drive innovation demand, but resource constraints may lead employees to adopt deviant innovation strategies. The impact of deviant innovation remains debated, and the role of transformational leadership in this process needs further exploration. Objective: This study examines how transformational leadership influences deviant innovation and the mediating roles of employees’ innovation self-efficacy and work mission. Methods: A survey of 237 virtual R&D team members from high-tech firms in Southwest China was conducted. Structural equation modelling (SPSS 26.0, Amos 26.0) was used to analyse the relationship between transformational leadership and deviant innovation. Results: This study is limited to virtual R&D teams in Southwest China, and future research should expand to other regions and industries. The reliance on survey data may introduce subjectivity, which could be mitigated through interviews or company records. Conclusion: Transformational leadership indirectly drives deviant innovation by enhancing employees’ innovation self-efficacy and work mission, both of which serve as partial mediators.